Does Corporate Social Responsibility (CSR) Reinforce Brand Equity? Evidence from Truely Essential - Kavya , P.S. (International Journal of Psychosocial Rehabilitation, 2020)
The purpose with which the study was undertaken is to identify is there any relationship between corporate social responsibility and brand equity, to identify the relation between two variables, we have used chi- square test. Truely essential company has conducted CSR activity for the wellbeing of the society where they are operating. On the other hand, to know that the society those who are benefited through CSR activity conducted by Truely essential company are loyal to the company. For this study we have collected the primary data from company as well as customer or society those who are benefited from CSR activity. From chi-square test we came to know there is no significant relation between CSR activity and brand equity. We collected the data from 50 respondents in Mysore using random sampling method. This study tells that CSR activity and brand equity are two different fact of the company where CSR activity helps the customer to identify the brand or company but it is not necessary to buy the products.